Growth Diversity, Total Phenol, and Flavonoid of Various Cayenne Pepper (Capsicum frutescens) Genotypes Under Shading Stress - Darmawansyah, Darmawansyah; Chozin, Muhamad Achmad; Santosa, Edi; Ritonga, Arya Widura (Department of Agronomy and Horticulture, IPB University, 2025)
The study of adaptation mechanisms in cayenne pepper under shade stress is crucial for further exploration. Cayenne pepper is one of the primary commodities that play an essential role in the agricultural industry. This research focuses on the adaptation of morphological, physiological, and secondary metabolite characteristics of cayenne pepper under shading treatments, while also examining the role of microclimate on these characteristics. The study was conducted from August 2023 to February 2024 at the Leuwikopo experimental field of Bogor Agricultural University, using five genotypes of cayenne pepper cultivated under two shading treatments: 0% and 50% shading, achieved using shade netting. The results showed that among the five genotypes tested, shade-loving genotypes, such as “Bonita,” and shade-tolerant genotypes, like “Ori 212,” displayed a greater morphological response in terms of plant height and canopy width under 50% shade compared to the other genotypes. In terms of yield traits, shade-tolerant genotypes, such as “Ori 212”, exhibited the highest fruit weight per plant under a 50% shading treatment compared to the other genotypes. Regarding physiological responses, specifically pigment content, no significant effect of shading treatment was observed. However, in terms of secondary metabolite content, all genotypes responded by increasing total phenol and flavonoid levels when grown in unshaded conditions or under full light intensity. This study provides insights into the adaptive responses of various cayenne pepper genotypes to microclimatic conditions in their growing environment.